(untitled) - Daniels, Arlene Kaplan (New York, 1990)
The work of the indefatigable Alice Hanson Cook benefitted the lives of working people-and especially working women-on four continents. A pioneer in union organizing, worker education, and equal rights for working women, Cook carried on her path-blazing work across the country and around the world, across racial, ethnic, national, and class lines, and across boundaries she refused to accept were impassable.
Keywords: Cook, alice hanson,Women labor leaders,Women college teachers,Feminists; Biography,Biography,Biography; United states,United states,United states